2006
DOI: 10.1140/epja/i2005-10294-8
|View full text |Cite
|
Sign up to set email alerts
|

Thermalization of gluons at RHIC: Dependence on initial conditions

Abstract: We investigate how thermalization of gluons depends on the initial conditions assumed in ultrarelativistic heavy ion collisions at RHIC. The study is based on simulations employing the pQCD inspired parton cascade solving the Boltzmann equation for gluons. We consider independently produced minijets with p T > p 0 = 1.3 ∼ 2.0 GeV and a color glass condensate as possible initial conditions for the freed gluons. It turns out that full kinetic equilibrium is achieved slightly sooner in denser system and its times… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
6
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 13 publications
7
6
0
Order By: Relevance
“…The quick thermalization and the smallness of the η/s ratio observed in the present calculations with the CGC initial conditions are consistent with the findings from the previous studies [5,6,13,28,29] using the Glauber-type minijets initial conditions. This demonstrates that independent of the chosen initial conditions, the pQCD bremsstrahlung processes (and the back reactions) dominate the dynamical equilibration and then keep the system behaving like a nearly perfect fluid.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The quick thermalization and the smallness of the η/s ratio observed in the present calculations with the CGC initial conditions are consistent with the findings from the previous studies [5,6,13,28,29] using the Glauber-type minijets initial conditions. This demonstrates that independent of the chosen initial conditions, the pQCD bremsstrahlung processes (and the back reactions) dominate the dynamical equilibration and then keep the system behaving like a nearly perfect fluid.…”
Section: Discussionsupporting
confidence: 93%
“…Therefore, the time scale of thermalization is of order α −2 s (ln α s ) −2 Q −1 s , which is smaller than the "Bottom-Up" prediction. The quick thermalization observed here is consistent with the findings from the previous studies [5,6,13]: The gluon bremsstrahlung favors initial condition with α s = 0.2 and Q s = 3 GeV could be appropriate for Pb-Pb collisions at the maximal energy at the LHC. In this case the gluon number also decreases at the beginning.…”
Section: Time Scale Of Thermalizationsupporting
confidence: 91%
“…The quick thermalization and the smallness of the η/s ratio observed in the present calculations with the CGC initial conditions are consistent with the findings from the previous studies [4,5,12,16,17] using the Glauber-type minijets initial conditions. This demonstrates that independent of the chosen initial conditions, the pQCD bremsstrahlung processes (and the back reactions) dominate the dynamical equilibration and then keep the system behaving like a nearly perfect fluid.…”
Section: Discussionsupporting
confidence: 93%
“…The dependence on α s proves to be weaker than the "Bottom-Up" prediction but consistent with the scaling obtained in [16]. The reason for the quick thermalization observed in our calculations is the gluon bremsstrahlung, which favors large-angle radiation due to the LPM suppression [4,5,12]. Thus, the pQCD gg ↔ ggg processes are dominant for the thermal equilibration.…”
Section: Introductionsupporting
confidence: 87%
“…In [2] it is demonstrated that the inelastic processes dominate the total transport collision rate and thus contribute much stronger to momentum isotropization then elastic ones. Within a default setting of minijet initial conditions, the overall build up of elliptic flow v 2 can be reasonably described [4] (a more dedicated study is presently undertaken [5]).…”
mentioning
confidence: 99%